Ð˜Ð·Ð¼ÐµÐ½ÐµÐ½Ð¸Ðµ Ð°Ð½Ñ‚Ð¸Ð¾ÐºÑÐ¸Ð´Ð°Ð½Ñ‚Ð½Ñ‹Ñ… ÑÐ²Ð¾Ð¹ÑÑ‚Ð² ÑÐºÑÑ‚Ñ€Ð°ÐºÑ‚Ð¾Ð² Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð¿Ð¾ÑÐ»Ðµ Ð·Ð°Ð¼Ð¾Ñ€Ð°Ð¶Ð¸Ð²Ð°Ð½Ð¸Ñ - Rozanova, S. L.; Naumenko, E. I.; Rozanova, E. D.; Nardid, O. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2010)
The experimental data, obtained under comparative evaluation of different freeze-thawing protocols' influence on human placenta extract antioxidant activity, estimated by capacity to reduce the ferric iron and ABTS+ radical, to chelate ferrous ions, to scavenge hydrogen peroxide and also by phenolic compound content, have been presented. Slow freezing of the extracts down to –20°С has been shown to cause the lowering of its activity, while rapid freezing down to –196°С increases the activity due to protein antioxidants' conformational changes.